Report of proceedings at a deputation to the Earl of Birkenhead - Labour Party (Great Britain) ; Trades Union Congress ; Mineworkers' Federation of Great Britain ; Birkenhead, Frederick Edwin Smith, Earl of, 1872-1930
9 December 1926